2021
DOI: 10.1001/jamanetworkopen.2020.32779
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality Among Young Adults Born Preterm and Early Term in 4 Nordic Nations

Abstract: IMPORTANCE Adverse long-term outcomes in individuals born before full gestation are not confined to individuals born at extreme gestational ages. Little is known regarding mortality patterns among individuals born in the weeks close to ideal gestation, and the exact causes are not well understood; both of these are crucial for public health, with the potential for modification of risk. OBJECTIVE To examine the risk of all-cause and noncommunicable diseases (NCD) deaths among young adults born preterm and early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 45 publications
4
85
2
Order By: Relevance
“…As such, ECV is now recognized as a novel prognostic marker independent of noninfarction scar in the myocardium ( 27 ). In our present study of normotensive individuals, we identified that nearly 9% of the preterm population had ECV of 30% or greater, which may contribute to their greater risk for early heart failure ( 4 ) and early cardiovascular-related mortality ( 7 ). Our finding of greater ECV with no change in native T1 in the preterm-born adults suggests a specific association with collagen deposition.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As such, ECV is now recognized as a novel prognostic marker independent of noninfarction scar in the myocardium ( 27 ). In our present study of normotensive individuals, we identified that nearly 9% of the preterm population had ECV of 30% or greater, which may contribute to their greater risk for early heart failure ( 4 ) and early cardiovascular-related mortality ( 7 ). Our finding of greater ECV with no change in native T1 in the preterm-born adults suggests a specific association with collagen deposition.…”
Section: Discussionmentioning
confidence: 85%
“…Preterm birth (<37 gestational weeks) affects >10% of live births worldwide ( 1 ) and abruptly interrupts the trajectory of cardiac development, leading to neonatal ( 2 ) and long-term ( 3 ) morbidity. Large-scale birth registries investigating the impact of being born preterm have shown an increased risk for cardiovascular diseases by childhood and adulthood, including heart failure ( 4 , 5 ), ischemic heart disease ( 6 ), and early cardiovascular-related mortality ( 7 ).…”
mentioning
confidence: 99%
“…Two previous studies evaluated the association between short gestation and the risk of stroke. No significant association was seen for prematurity and the risk of fatal stroke (21) or stroke events (22). In the present study, we included men born between 1945 and 1961, but because information on gestational age was J o u r n a l P r e -p r o o f not available, prematurity could not be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis may develop from early childhood onwards, but manifests symptomatically as cardiovascular disease (CVD) in adulthood (1, 2) and it remains the most common cause of death globally (3,4). Preterm infants are at increased risk for developing CVD in adulthood (5,6), with some estimates suggesting a doubling of risk compared to those born at term (7). This heightened risk may reflect the increased inflammatory exposures that characterise pregnancies that culminate in preterm birth, including prenatal inflammation (chorioamnionitis) and that arising from early life infections, which are highly prevalent in preterm infants (8).…”
Section: Introductionmentioning
confidence: 99%